PENGARUH UPAH, KERJASAMA ANTAR KARYAWAN, DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA PADA PT. OSKSA ART STUDIO BANTUL YOGYAKARTA - Fanita Achmad; Utik Bidayati (Universitas Ahmad Dahlan, 2012)
The purpose of this study to determine the effect of wages, cooperation among employees and work environment on morale at the Art Studio PT.Osksa either partially or in unison. Population in this study were all employees of PT. Osksa Art Studio Bantul, Yogyakarta. The sampling technique using the method of Non-Probability Sampling, then used purposive sampling. Characteristics of the sampled respondents are employees working in PT. Art Studio Osksa aged 17 years and over. The data was collected by distributing questionnaires to a sample which numbered 70 people. Result showed that the variable wages and work environment partially having a significant effect on morale, while the variable partial cooperation among the employees had no significant effect on morale. The wages, cooperation among employees and work environment simultaneously have significant impact on morale at PT.Osksa Art Studio.